Characteristics of energy storage and dissipation of coal under one‐time cyclic load. Issue 9 (1st June 2020) - Peng, Kang; Shi, Shaowei; Zou, Quanle; Mou, Junhui; Yu, Jin; Zhang, Yongjiang; Cheng, Yanying
Abstract: Energy is an important research parameter in rock mechanics. To explore the law of energy evolution of coal, a one‐time loading and unloading test under uniaxial compression was conducted on coal taken from four different coal mines. By utilizing the area integral method, the total input, elastic, and dissipated energy densities in coal at different unloading levels were calculated. The correlation between various energy densities and the evolution law of energy density with different unloading levels was attained. The peak strengths of the coal slowly declined with an increasing unloading level, which conforms to the relation of a linearly decreasing function. The energy dissipation rate has nonlinear characteristics, and the shape of the dissipation rate fitting curve changed from an upper concave to a downward concave with increasing strength. In all the coal samples, the energy density grew nonlinearly with the unloading level. Moreover, the growth rate of the total energy density was the highest, followed by the growth rates of the elastic and dissipated energy densities. All ratios of the elastic and dissipated energy densities to the total input energy density and the ratio of the dissipated energy density to the elastic energy density were constant. As the strength increased, the input energy and the elastic energy density increased at a faster rate, and they observed the same law. There is an insignificant relationship between the degree of destruction of the coal and the level of unloading. Energy is a major factor that drives the failure of a test piece, but this is not the main factor that determines the degree of damage to the test piece. Abstract : Characteristics of energy storage and dissipation of coal under one‐time cyclic loads were revealed.